2004
DOI: 10.1063/1.1811672
|View full text |Cite
|
Sign up to set email alerts
|

A priori and a posteriori tests of inflow conditions for large-eddy simulation

Abstract: Comparisons of inflow conditions for large-eddy simulations of turbulent, wall-bounded flows are carried out. Consistent with previous investigations, it is found that the spectral content of the inflow velocity is important. Inflow conditions based on random-noise, or small-scale eddies only, dissipate quickly. Temporal and spatial filtering of a time series obtained from a separate calculation indicates that it is important to capture eddies of dimensions equal to or larger than the integral length scale of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
142
0
11

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 262 publications
(165 citation statements)
references
References 23 publications
4
142
0
11
Order By: Relevance
“…Recall that, as noted earlier, Keating et al (2004) used Batten et al (2004)'s procedure (i.e. a synthetic turbulence generation method) to generate inflow data for a plane channel flow and found that the redevelopment was slow requiring at least 20d.…”
Section: Plane Channel Flows Using the New Inflow Conditionmentioning
confidence: 92%
See 2 more Smart Citations
“…Recall that, as noted earlier, Keating et al (2004) used Batten et al (2004)'s procedure (i.e. a synthetic turbulence generation method) to generate inflow data for a plane channel flow and found that the redevelopment was slow requiring at least 20d.…”
Section: Plane Channel Flows Using the New Inflow Conditionmentioning
confidence: 92%
“…Alternatively, a time-evolving LES or direct numerical simulation (DNS) with a periodic (Garcia et al, 2004;Keating et al, 2004) or a 'modified periodic' (Lund et al, 1998) inlet-outlet boundary condition can be used to generate appropriate turbulent flow. The latter authors used a sort of 'precursor simulation', in which the velocity field at an appropriate downstream station is stored and imposed in suitably re-scaled form as inflow data for the primary computation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this is only true as long as the prescribed length scales are at least as large as the integral length scales of the real flow. Failing to meet that requirement can lead to laminarization issues [29,52] just as when only white noise is added to the flow. The prescribed mean-velocity profile was obtained from the semi-analytical method described in Li [31] and the prescribed Reynolds stresses were obtained from an earlier simulation under similar flow conditions as the one considered here.…”
Section: Inflow Boundary Conditionsmentioning
confidence: 99%
“…Kraichnan's turbulence generator was used in many subsequent studies to model aeroacoustic noise, [2][3][4] inlet boundary conditions, [5][6][7][8][9][10] verification and validation of turbulence solvers, 11,12 and a priori and a posteriori testing of turbulence models. 13,14 To enforce a divergence-free velocity field, Kraichnan's method requires that two vectors be perpendicular. In this comment we show that this condition is only valid in the infinitesimal limit and should be replaced with an otherwise simple modification based on the discrete divergence of the velocity field.…”
Section: Introductionmentioning
confidence: 99%